Kinetic and Thermodynamic Investigations of the Oxidation of Some Perfumery Alcohols - Prabhu, D.V.; A. Parbat, Harichandra; A. Tandel, Muzaffar (Asian Journal of Chemistry, 2011)
Primary acyclic alcohols, nerol, citronellol and geraniol and secondary cyclic alcohols, borneol, isoborneol and menthol are used in the manufacture of perfumes, fragrances, cosmetics and flavours. Some aliphatic alcohols are extensively used as diluents in the perfumery industry. The kinetics studies of the controlled oxidation of these three classes of perfumery alcohols by sodium N-chlorobenzene-p-sulphonamide (chloramine-T) have been carried out in alkaline medium. The oxidation of all the six aliphatic alcohols has been carried out in the micellar phase using sodium dodecylsulphate surfactant. The effects of alcohol concentration, oxidant concentration, temperature and ionic strength on the reaction rate have been studied in detail and suitable reaction mechanisms and rate laws have been suggested. The thermodynamic activation parameters of the oxidation reaction have been evaluated from the temperature dependence of the rate in the range 303-318 K. The rate determining step of the oxidation reaction has been identified. The rate laws suggest a first order dependence on alcohol and oxidant concentrations and inverse first order dependence on OH– ions. The oxidation is retarded at higher concentrations of the oxidant. The oxidation rates follow the sequences; (1) geraniol > nerol > citronellol for the primary acyclic alcohols; (2) borneol > isoborneol > menthol for the secondary cyclic alcohols; (3) 1-propanol > 3-methyl-1-butanol > 1-butanol > 1-hexanol for the primary aliphatic alcohols; (4) 2-propanol >2-butanol for the secondary aliphatic alcohols. The sequences have been discussed on the basis of the steric factors, structures and isomeric characteristics of the alcohols under study. In general, it is observed that, as expected, primary acyclic alcohols are more susceptible to oxidation than secondary cyclic alcohols.